Physiological, anatomical and antioxidant responses to salinity in the Mediterranean pastoral grass plant Stipa lagascae - Abdellaoui, Raoudha; Boughalleb F.; Chebil, Zohra; Mahmoudi, Maher; Belgacem, Azaiez (Commonwealth Scientific and Industrial Research Organisation, 2017)
Soil and water salinity is a major environmental problem in the dry Mediterranean regions, affecting rangeland production. This study investigated the effects of salinity on the wild perennial grass (Poaceae) species Stipa lagascae R. & Sch., a potential forage plant that could be used to rehabilitate degraded rangelands in dry areas. In a laboratory, 3-month-old S. lagascae seedlings were subjected to increasing salt treatments (0–400 mm NaCl) for 45 days. Physiological and biochemical parameters such as leaf water potential (Ψw), leaf relative water content (RWC), proline, total soluble sugars, Na+, K+ and Ca2+ contents, and catalase, ascorbate peroxidase and glutathione reductase activities were measured. Total soluble sugars and proline concentrations increased and Ψw and RWC decreased with increasing salt concentrations. Lower salt concentrations induced a non-significant degradation of chlorophyll pigments. Shoot Na+ content increased with a salinity level, whereas shoot K+ and Ca2+ concentrations decreased and the K+ : Na+ ratio was lower. The salinity threshold, above which S. lagascae showed signs of damage, occurred at 300 mm. Plants have evolved reactive oxygen species (ROS) scavenging enzymes including catalase, ascorbate peroxidase and glutathione reductase, which provide cells with an efficient mechanism to neutralise ROS. The tolerance strategies of S. lagascae to moderate salinity seem to include osmotic adjustment through total soluble sugars and proline accumulation, and highly inducible antioxidative defence. Further investigations are necessary to study the effect of salt stress on distribution of ions (Na+, K+, Ca2+, Mg2+, Cl–, NO3–, SO42–) and osmotic adjustment. Photosynthesis and water-use efficiency parameters could be also useful tools.